Constant low-to-moderate mechanical asymmetries during 800-m track running - Girard, O.; Millet, G. P.; Micallef, J.-P. (Frontiers in Sports and Active Living, 2024)
Introduction Modifications in asymmetry in response to self-paced efforts have not been thoroughly documented, particularly regarding horizontally-derived ground reaction force variables. We determined the magnitude and range of gait asymmetries during 800 m track running.